Accounting for soil parameter uncertainty in a physically based and distributed approach for rainfall‐triggered landslides. Issue 6 (15th October 2015) - Arnone, E.; Dialynas, Y. G.; Noto, L. V.; Bras, R. L.
Abstract: In this study we propose a probabilistic approach for coupled distributed hydrological‐hillslope stability models that accounts for soil parameters uncertainty at basin scale. The geotechnical and soil retention curve parameters are treated as random variables across the basin and theoretical probability distributions of the Factor of Safety (FS) are estimated. The derived distributions are used to obtain the spatio‐temporal dynamics of probability of failure, in terms of parameters uncertainty, conditioned to soil moisture dynamics. The framework has been implemented in the tRIBS‐VEGGIE (Triangulated Irregular Network (TIN)‐based Real‐time Integrated Basin Simulator‐VEGetation Generator for Interactive Evolution)‐Landslide model and applied to a basin in the Luquillo Experimental Forest (Puerto Rico) where shallow landslides are common. In particular, the methodology was used to evaluate how the spatial and temporal patterns of precipitation, whose variability is significant over the basin, affect the distribution of probability of failure, through event scale analyses. Results indicate that hyetographs where heavy precipitation is near the end of the event lead to the most critical conditions in terms of probability of failure. Copyright © 2015 John Wiley & Sons, Ltd.